19.2: Distinguished Paper: Characterization of Electron‐Hole Pair Migration and Trapping in Rare Earth Doped YBO3 under Vacuum Ultraviolet Excitation. Issue 1 (1st July 2013) - Wallace, Max; Diaz, Anthony L.
Abstract: We have measured host‐to‐activator energy transfer efficiencies in rare‐earth doped YBO3 under vacuum ultraviolet excitation. From these data, relative electron‐hole (e‐h) pair trapping rate constants can be estimated. Our analysis suggests a correlation between e‐h trapping efficiency and the energy of activator electronic states relative to the host conduction band.